Financial performance and financial position analysis of Reckitt Benckiser (Bangladesh) PLC - Bhowmick, Pritu (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.